The Importance of Including Maternal Immune Activation in Animal Models of Hypoxic–Ischemic Encephalopathy - Bailey Collins; Elise A. Lemanski; Elizabeth Wright-Jin (Biomedicines)
Hypoxic–ischemic encephalopathy (HIE) is a perinatal brain injury that is the leading cause of cerebral palsy, developmental delay, and poor cognitive outcomes in children born at term, occurring in about 1.5 out of 1000 births. The only proven therapy for HIE is therapeutic hypothermia. However, despite this treatment, many children ultimately suffer disability, brain injury, and even death. Barriers to implementation including late diagnosis and lack of resources also lead to poorer outcomes. This demonstrates a critical need for additional treatments for HIE, and to facilitate this, we need translational models that accurately reflect risk factors and interactions present in HIE. Maternal or amniotic infection is a significant risk factor and possible cause of HIE in humans. Maternal immune activation (MIA) is a well-established model of maternal infection and inflammation that has significant developmental consequences largely characterized within the context of neurodevelopmental disorders such as autism spectrum disorder and schizophrenia. MIA can also lead to long-lasting changes within the neuroimmune system, which lead to compounding negative outcomes following a second insult. This supports the importance of understanding the interaction of maternal inflammation and hypoxic–ischemic outcomes. Animal models have been invaluable to understanding the pathophysiology of this injury and to the development of therapeutic hypothermia. However, each model system has its own limitations. Large animal models such as pigs may more accurately represent the brain and organ development and complexity in humans, while rodent models are more cost-effective and offer more possible molecular techniques. Recent studies have utilized MIA or direct inflammation prior to HIE insult. Investigators should thoughtfully consider the risk factors they wish to include in their HIE animal models. In the incorporation of MIA, investigators should consider the type, timing, and dose of the inflammatory stimulus, as well as the timing, severity, and type of hypoxic insult. Using a variety of animal models that incorporate the maternal–placental–fetal system of inflammation will most likely lead to a more robust understanding of the mechanisms of this injury that can guide future clinical decisions and therapies.